2011
DOI: 10.1002/jmri.22713
|View full text |Cite
|
Sign up to set email alerts
|

Optimized high‐resolution contrast‐enhanced hepatobiliary imaging at 3 tesla: A cross‐over comparison of gadobenate dimeglumine and gadoxetic acid

Abstract: Purpose To evaluate the SNR and CNR performance of 0.05 mmol/kg gadoxetic acid and 0.1 mmol/kg gadobenate dimeglumine for dynamic and hepatobiliary phase imaging. In addition, flip angles (FA) that maximize relative contrast-to-noise performance for hepatobiliary phase imaging were determined. Materials and Methods A cross-over study in ten volunteers was performed using each agent. Imaging was performed at 3T with a 32-channel phased-array coil using breath-held 3D spoiled gradient echo sequences for SNR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 35 publications
2
52
0
Order By: Relevance
“…Hepatic vascular SNR was lower in the Gd-EOB-DTPA group despite doubling the FDAapproved dose, and it was suggested that this agent be reserved for cases in which hepatobiliary phase imaging is needed [7]. Therefore, it should not be surprising that a hypervascular lesion such as HCC should show relatively lower early dynamic enhancement with Gd-EOB-DTPA compared to Gd-BOPTA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic vascular SNR was lower in the Gd-EOB-DTPA group despite doubling the FDAapproved dose, and it was suggested that this agent be reserved for cases in which hepatobiliary phase imaging is needed [7]. Therefore, it should not be surprising that a hypervascular lesion such as HCC should show relatively lower early dynamic enhancement with Gd-EOB-DTPA compared to Gd-BOPTA.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, Gadobenate dimeglumine (Gd-BOPTA) undergoes 78-96% renal excretion and therefore yields a lower percentage of hepatocyte enhancement in the hepatobiliary phase when compared to Gd-EOB-DTPA [7]. Page | 6…”
Section: Page |mentioning
confidence: 99%
“…We used muscle as a surrogate for weakly enhancing liver lesions such as hypovascular metastasis. 7,18 We used the following equations to calculate the SNR of the liver, portal vein, and muscle:…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…In fact, many institutions have adopted the use of higher doses, such as a fixed dose of 10 mL rather than a dose based on patient weight, as a standard in clinical MR imaging. [18][19][20] For patients weighing 50 to 100 kg, this results in effective doses of 0.025 to 0.05 mmol/kg. Considering that a dose of 0.025 mmol/kg of gadolinium is only a quarter of the conventional MR contrast agent dose, the expected risk of toxicity from dose escalation is likely to be minimal.…”
Section: Introductionmentioning
confidence: 99%
“…33 Coronal or sagittal images of good quality can be reconstructed from the isovoxel axial images with submillimeter spatial resolution. 33,34 How to shorten examination time A 20-min waiting period for the hepatocyte phase is su‹cient to obtain other sequences, so many researchers have attempted to shorten examination time by obtaining T 2 -weighted and diŠu-sion-weighted images after gadoxetic acid administration. Acquisition of T 2 -weighted images after gadoxetic acid injection has been demonstrated without compromise of image contrast.…”
Section: Rules For the Hepatocyte Phase Delay Before Hepatocyte Phasementioning
confidence: 99%